Expectation Traps and Monetary Policy - Albanesi, Stefania; Chari, V. V.; Christiano, Lawrence J. (Review of Economic Studies, 2003)
Why is inflation persistently high in some periods and low in others? The reason may be the absence of commitment in monetary policy. In a standard model, absence of commitment leads to multiple equilibria, or expectation traps, even without trigger strategies. In these traps, expectations of high or low inflation lead the public to take defensive actions, which then make accommodating those expectations the optimal monetary policy. Under commitment, the equilibrium is unique and the inflation rate is low on average. This analysis suggests that institutions which promote commitment can prevent high inflation episodes from recurring.